Integrated marketing communication advertising and promotion in a digital world - Juska, Jerome M. (New York Routledge, 2018)
"This book shows students how to achieve their marketing objectives through a campaign that coordinates marketing, advertising, and promotion."--Back cover.
What is integrated marketing communications? -- Digital media environments -- IMC budgets and objectives -- Brand research and consumer insights -- Target audiences and segmentation -- Creative development -- Media planning methods -- Advertising campaigns -- Sales promotion strategies -- Brand visibility programs -- Public relations strategies -- The IMC plan.
Keywords: Internet advertising; Internet marketing